Proof of the effectiveness of using the methods of studying the fungus damage to the cereals in the learning process through the pedagogical experiment (Journal of Educational Sciences, 2019)
The article discusses the issues of the research activity of biological teachers. The biological experiment was tested in pedagogical practice with a specially developed methodology using biological information. At the same time, a review of the work of domestic and foreign methodologists was carried out and guided by pedagogical practice. The pedagogical experiment was carried out in 2017-2019 at the Kazakh National University named after al-Farabi with participation of the 2nd year students of 5B011300-Biology specialty. Students involved in the teaching experiments were divided into two groups: control and experimental group. The pedagogical experiment consisted of 3 stages: the definition, the formation and the result of the conclusion or control. Theoretical conclusions on the research problem at each stage were experimentally tested and the results achieved, summarized and summarized allowed identifying the initial stage of the future researchers' biological research. At the initial stage of the research, the students of two groups were interviewed for mushrooms, which cereal affected the breeders. At the second stage, students of the experimental group acquainted with methods of studying the fungus of the cereals and developed researches. In the third stage, the students received a repeat survey to determine the results of the pedagogical experiment.Key words: fungi, grains, seed crops, ecology of fungi, pedagogical experiment, research ability.